1979
DOI: 10.1346/ccmn.1979.0270308
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Adsorbed and Structural Iron in Hectorite as Indicated by Oxidation of Benzidine

Abstract: Abstract--The roles of different forms of Fe(III) impurities in a hectorite with respect to the oxidation of benzidine in aqueous suspension have been evaluated using electron spin resonance and UV-visible spectroscopy. Natural surface-adsorbed Fe(III) showed no detectable activity in the oxidation process, while very small quantities of structural octahedral Fe(III) apparently promoted a relatively rapid conversion to the radical cation. However, extremely small quantities of benzidine were oxidized in compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Tennakoon et al (1974) presented direct Mtssbauer spectroscopic evidence for the involvement of structural iron(III) in the oxidation-reduction process leading to the formation of colored benzidine radical cations in montmorillonite. Recent work by McBride (1979) has shown that clay-edge aluminum sites are relatively unimportant in the oxidation of benzidine.…”
Section: Introductionmentioning
confidence: 99%
“…Tennakoon et al (1974) presented direct Mtssbauer spectroscopic evidence for the involvement of structural iron(III) in the oxidation-reduction process leading to the formation of colored benzidine radical cations in montmorillonite. Recent work by McBride (1979) has shown that clay-edge aluminum sites are relatively unimportant in the oxidation of benzidine.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of colored clayorganic complexes is well documented (Hauser et al, 1941;Solomon et al, 1968;Theng, 1971;Voudrias and Rienhard, 1986), and has been related to transformation reaction intermediates, and products at the clay surface Theng, 1971;Soma et al, 1984Soma et al, , 1985Soma et al, , 1986Furukawa and Brindley, 1973;Cloos et aL, 1981). Color development is often ascribed to charge transfer reactions (McBride, 1979;Soma et al, 1984Soma et al, , 1985Soma et al, , 1986Teenakoon et al, 1974), but color development and intensity are dependent on the clay type (Hauser et al, 1941;Voudrias and Rienhard, 1986;Thompson and Moll, 1973), reaction mechanism (Fenn et aL, 1973), and saturating inorganic cation (Furukawa and Brindley, 1973;Soma et al, 1983;Vansant and Yariv, 1977). The formation of a colored complex in the montmorillonite-benzidine system is the result of benzidine sorption and subsequent oxidation to a radical cation by the reduction of structural ferric iron; although 02, or freshly sorbed Fe 3 § and Cu 2 § can also act as oxidants (McBride, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Clay surfaces have the capacity to act as catalysts in chemical oxidation/reduction, acid-base neutralization, and hydrolysis reactions (McBride, 1979;Theng, 1974;Solomon, 1968). The formation of colored clayorganic complexes is well documented (Hauser et al, 1941;Solomon et al, 1968;Theng, 1971;Voudrias and Rienhard, 1986), and has been related to transformation reaction intermediates, and products at the clay surface Theng, 1971;Soma et al, 1984Soma et al, , 1985Soma et al, , 1986Furukawa and Brindley, 1973;Cloos et aL, 1981).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations